2021
DOI: 10.1007/s10841-021-00331-w
|View full text |Cite
|
Sign up to set email alerts
|

Partial mowing of urban lawns supports higher abundances and diversities of insects

Abstract: Within the citizen science project “Flowering meadows for Saxonian butterflies”, more than 640 meadows are partially and at maximum three times annually mowed in order to change urban lawns into habitats for insects. In 2019, insect diversity was evaluated using the 100 sweep net technique during five visits at nine butterfly meadows (BM) and nine intensively mowed lawns (IML). The mean arthropod biomass of these five visits per site is significantly higher on BM compared to IML. All adult individuals of Apida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, a plan of management of the grass lawns, with less intensive mowing, is recommended to maintain viable populations of invertebrates throughout the year, resulting in higher abundance and diversity in these groups (e.g. Lerman et al 2018;Wintergerst et al 2021), a pattern also reported for grazing systems (Schtickzelle et al 2007). Such a result could be especially important considering that similar decreases in insect richness and abundances are mirrored by other invertebrates (Gibson et al 1992;Ausden et al 2005), especially during the dry season, affecting the available food supply for local populations of birds, small mammals, lizards and frogs in the study area.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a plan of management of the grass lawns, with less intensive mowing, is recommended to maintain viable populations of invertebrates throughout the year, resulting in higher abundance and diversity in these groups (e.g. Lerman et al 2018;Wintergerst et al 2021), a pattern also reported for grazing systems (Schtickzelle et al 2007). Such a result could be especially important considering that similar decreases in insect richness and abundances are mirrored by other invertebrates (Gibson et al 1992;Ausden et al 2005), especially during the dry season, affecting the available food supply for local populations of birds, small mammals, lizards and frogs in the study area.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond these direct effects, mowing also reduces the availability and diversity of plant species, so that feeding specialists can no longer find suitable host plants for reproduction and adults are subjected to reduced nectar availability (Halbritter et al, 2015). While some mowing or other management is necessary for grassland insects to prevent succession into woodland, high mowing intensity consistently reduces the abundance and species richness of moths and other insects and leads to changes in community composition such as reduction of habitat specialists (Chisté et al, 2016; Mangels et al, 2017; Wintergerst et al, 2021). However, once grasslands and green spaces are mown less often, plant and insect diversity increases (Chollet et al, 2018; Sehrt et al, 2020; Wastian et al, 2016), which is why reducing mowing intensity is a promising strategy for promoting urban insect diversity, including Lepidoptera (Proske et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Mortality due to mowing can be high and mowing reduces the availability of suitable sites for larval development in many insects. Thus, only a few species can reproduce in intensively mown urban green spaces (Wintergerst et al, 2021). Furthermore, urban areas tend to be more affected by air pollution and light pollution than surrounding habitats adjacent to cities (Knop et al, 2017; van Langevelde et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat, resource or management attributes that support insect diversity are not always suitable for, or desirable in, human‐used spaces. Weedy floral resources may be ideal for insects but can be perceived as messy by people (Lowenstein et al, 2019), and this impedes the many benefits of reduced mowing frequency (Wintergerst et al, 2021). Elements such as carrion are an even greater challenge in urban areas (Barton et al, 2013).…”
Section: Priorities For Urban Insect Ecology Research and Conservationmentioning
confidence: 99%